Negotiating beauty in Pakistan: A qualitative exploration of body image, nutrition, and cultural ideals among young women in Azad Jammu & Kashmir - Sajal Bint-e-Khalil; Inayat Ali (Dialogues in Health)
Beauty is not a static or universal phenomenon. However, it is a dynamic ideal shaped by sociocultural patterns and practices. Particulalry, multiple sociocultural patterns prevail regarding how a female body should be maintained, displayed, and evaluated. Media representations, in particular, play a central role in reinforcing and circulating narrow, idealized, and often unattainable beauty standards, contributing to a system in which women are disproportionately subject to stringent aesthetic scrutiny. This phenomenological study explores the sociocultural construction of beauty and its experience as well as internalization among young women in Azad Jammu & Kashmir, Pakistan. We used in-depth interviews to explore and understand how participants perceive the relationship between beauty and nutrition, revealing a deeply embedded tension between individual experience and cultural expectations. While approximately half of the participants defined beauty in terms of physical appearance, the remainder emphasized internal traits such as personality and behavior. Notably, nearly 45 % of respondents believed that beauty is objective rather than subjective, which suggests a limited engagement with internal or emotional dimensions of self-perception, and reflects the powerful influence of external social and cultural standards.